Scabies herpeticum, an emerging clinical form of crusted scabies in AIDS patient: case report and literature review (2018)
Scabies is a cutaneous ectoparasitosis caused by the mite, Sarcoptes scabiei variety hominis, which affects 130 million people worldwide every year. The risk factors include: overcrowded conditions, extended-care facilities, child care, and immunosuppressive conditions such as systemic immunosuppressive therapy, elderly, Down syndrome, mental disorders, malignant neoplasms, connective tissue diseases, metabolic disorders, leprosy, lymphotropic virus type 1, and acquired immunodeficiency syndrome (AIDS). As for the transmission, it usually occurs through direct skin-to-skin contact (sexual intercourse and other sexual behaviors with an infected sexual partner) and fomites such as infested bedding or clothing. Three types of scabies are clinically distinguished: classic scabies, nodular scabies, and crusted scabies (CS); the latter is the rarest presentation of this disease so far in which the failure of the cellular immune system of the host generates a super infestation of mites, which results in a great inflammatory reaction and secondary epidermal hyperkeratosis Crusted scabies represents a clinical challenge, because it can present with a severe and atypical course in immunosuppressed patients. Additionally, superposition with a simultaneous infection in the same site can generate diagnostic confusion, inadequate treatments, and risk of secondary irreversible sequelae